2017
DOI: 10.1007/s11104-017-3324-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical changes in organic matter after fungal colonization in a nitrogen fertilized and unfertilized Norway spruce forest

Abstract: Background and aims Decomposition and transformation of organic matter (OM) in forest soils are conducted by the concomitant action of saprotrophic and mycorrhizal fungi. Here, we examine chemical changes in OM after fungal colonization in nitrogen fertilized and unfertilized soils from a Norway spruce forest. Methods Sand-filled bags amended with composted maize leaves were placed in the forest soil and harvested after 17 months. Infrared and near edge X-ray absorption fine structure spectroscopies were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Therefore, elevated inorganic nutrient availability may favour this fungal genus. Similarly to our study,Mason et al (2020) found subtle increases in Russulales after P fertilization (5 years) of an LP forest (Ohio, USA) Nicolás et al (2017). found no significant effects of N fertilization on Russula sp.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, elevated inorganic nutrient availability may favour this fungal genus. Similarly to our study,Mason et al (2020) found subtle increases in Russulales after P fertilization (5 years) of an LP forest (Ohio, USA) Nicolás et al (2017). found no significant effects of N fertilization on Russula sp.…”
supporting
confidence: 85%
“…In boreal spruce forests, N fertilization caused a significant turnover of soil fungal communities, decreased fungal biomass, and increased the N:P ratio of the needles (Almeida et al 2019). Other studies reported only weak or no effect of N treatments on the fungal community structures (Nicolás et al 2017, Purahong et al 2018, Maaroufi et al 2019) and relationships with P mobilization were not detected (Forsmark et al 2020). Only few studies investigated fungal communities after P fertilization in forests.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the bags filled with sand reduce the ingrowth of nonmycorrhizal fungi compared to bags with sterile soil [ 57 ] and after the arrival of molecular methods that made it possible to analyse fungal communities inside sandbags, the results often confirmed that ectomycorrhizal fungi represent the majority of sandbag colonisers during the vegetation season [ 57 , 58 , 59 ]. Other reports, however, noticed the presence of other fungal guilds as well, indicating that the sandbags might reflect more the total fungal community in the studied soil than the ectomycorrhizal community only [ 31 , 56 , 60 , 61 , 62 ]. In our experimental system, we recorded a much smaller proportion of the ectomycorrhizal fungi on the total sandbag community compared to soil, especially in the winter months ( Figure 3 D).…”
Section: Discussionmentioning
confidence: 84%
“…However, Russulales showed a significant decrease in response to the combined P + N treatment and increased during spring in soils fertilized only with P. Similar to our study, Mason et al (2020) found subtle increases in Russulales after P fertilization (5 years) in an LP forest (Ohio, USA). Nicolás et al (2017) found no significant effects of N fertilization on Russula sp. in a boreal forest.…”
Section: N and P Inputs Affect The Phylogenetic And Functional Compositions Of Fungal Assemblagesmentioning
confidence: 78%
“…In boreal spruce forests, N fertilization was shown to cause a significant turnover of soil fungal communities, decrease fungal biomass, and increase the N:P ratio of the needles (Allison et al 2007;Almeida et al 2019). Other studies reported only weak or no effect of N treatments on the fungal community composition (Maaroufi et al 2019;Nicolás et al 2017;Purahong et al 2018), and relationships with P mobilization were not detected (Forsmark et al, 2021). Empirical studies and theoretical models suggest that EMF in temperate beech forests are less sensitive to N deposition than conifers (Lilleskov et al 2019;Rotter et al 2020;Taylor et al 2000), but it is unknown how N fertilization affects EMF and other soil fungi when N availability is increased under P shortage.…”
Section: Introductionmentioning
confidence: 99%